OPTIMALISASI PENGGUNAAN PERSONAL PROTECTIVE EQUIPMENT (PPE) DALAM UPAYA MENJAGA KESELAMATAN KERJA DI MV. TONASA LINE XV - Fazir Akbar Nugraha; I Kadek Laju; Bayu Yudho Baskoro; Rizal Rochmansyah (STKIP Subang, 2026)
This study aims to analyze the optimization of Personal Protective Equipment (PPE) use in an effort to maintain occupational safety on the MV. Tonasa Line XV. The study used a qualitative approach with data collection techniques through field observations, in-depth interviews with four key ship informants (Chief Officer, Bosun, Third Officer, and AB), and documentation. Data analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the availability of PPE on the ship has basically met the need for occupational protection, but the quality of some equipment has begun to decline and the use of additional protection is not evenly distributed. Crew compliance is relatively good in the use of helmets and safety shoes, but partial non-compliance is still found in the use of gloves and ear protectors which has the potential to cause minor work injuries. The safety control system through safety briefings and officer supervision has been implemented, although its effectiveness is not optimal because sanctions are still in the form of verbal warnings. On the other hand, the crew safety culture is relatively positive and is a major supporting factor in maintaining occupational safety, while the main weakness lies in the aspect of PPE maintenance and replacement that is not yet responsive. Therefore, optimizing the use of PPE requires strengthening behavioral discipline, a maintenance management system, and stricter enforcement of safety regulations to ensure sustainable occupational safety on ships.